A Normative Understanding of Innovation - Michels, Kevin H. (NOvation — Critical Studies of Innovation, 2022)
Commentators have bemoaned the absence of a clear conceptual understanding of innovation both generally and within responsible innovation (RI). Much of our thinking about innovation is fragmented into separate categories such as “business,” “social” or “technological” innovation with no clear understanding of the term these adjectives modify. In addition, RI discussions focus overwhelmingly on technological advances delivered through the marketplace, which are only a portion of the innovation story. Clearly, we need to develop a stronger account of the concept of innovation. What criteria must be satisfied for a contribution to the world to qualify as an innovation or, more simply, what is an innovation? This article will contend that innovation is inescapably normative, and that we can construct an understanding of innovation by elaborating on its normative elements and their implications. Innovation, I will propose, is ethical change that delivers substantial applied value to beneficiaries of a domain. After developing this account, I will show how it can reframe our understanding of innovation’s relationship with technology and the marketplace, the innovator’s understanding of technology, who gets to innovate, and why the various categories of innovation may be more diverting than helpful. I will also reflect on how the account of innovation offered here can refine our understanding of RI.